Repetition as a Path to Authentic Existence in Kierkegaard’s Work - Pavlikova, Martina; Tavilla, Igor (Journal of Education Culture and Society, 2023)
Thesis. The aim of the paper is to interpret Kierkegaard's concept of repetition as a way of creating and experiencing authentic existence in an environment that is set up to repeat this same, inauthentic content of consciousness.Concept. Repetition is associated with determinism and represents social stagnation. Repetition creates the conditions for an inauthentic existence. The article offers an interpretation of Kierkegaard's concept of repetition, which is the repetition of another and produces authentic existence.Results and conclusions. Repetition automatically produces of the same. The repetition of one's choice of oneself is a process of creating spirit and individuality, which is a fundamental principle of authentic existence. Creating an authentic personality is one of the ways to solve the current crisis in society, which is associated with an inauthentic experience of existence, abdication of responsibility and repetition of lies.Cognitive value. The postmodern society associated with the use of the media is not the cause of social disorientation. It is a means that an individual uses to repeat the same. The social environment and magic themselves are not negative, the negative is the inauthentic attitude of a person to them.